2019
DOI: 10.22328/2077-9828-2019-11-2-67-74
|View full text |Cite
|
Sign up to set email alerts
|

The Hiv and Tuberculosis Tendency in Penitentiary System of North-West Region of Russia

Abstract: The penitentiary system is one of the leading factors in preservation and the spread of HIV infection and tuberculosis epidemics among the general population. The aim of the analytical review is to assess the trends of the HIV and tuberculosis epidemics, as monoinfections in prisons, and to evaluate their influence on the general situation in the North-West Region. In the study were used data from the Rosstat and the Ministry of Justice annual reporting forms during 2007–2017. Results. Tuberculosis incidence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…In addition, our suggestion to conduct more detailed studies is supported by the disparities in HIV and TB incidence observed among the general population and the permanent residents of the Russian Arctic territories, which could be tied to differences in the level of impact of globalisation and migration processes on the epidemic situation in the regions. The high difference in HIV and TB incidence between the whole population and permanent residents in the Republics of Karelia and Komi, as well as in Arkhangelsk oblast, could be related to the epidemics in the penitentiary system [ 41 ], and the same assumption is eligible for Krasnoyarsk region [ 42 ]. The probable external impact on the HIV and TB incidence among permanent residents in Murmansk oblast and, interestingly, the huge prevailing of the TB incidence in the general population over the incidence among the permanent residents in NAD, are both phenomena that need clarification.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our suggestion to conduct more detailed studies is supported by the disparities in HIV and TB incidence observed among the general population and the permanent residents of the Russian Arctic territories, which could be tied to differences in the level of impact of globalisation and migration processes on the epidemic situation in the regions. The high difference in HIV and TB incidence between the whole population and permanent residents in the Republics of Karelia and Komi, as well as in Arkhangelsk oblast, could be related to the epidemics in the penitentiary system [ 41 ], and the same assumption is eligible for Krasnoyarsk region [ 42 ]. The probable external impact on the HIV and TB incidence among permanent residents in Murmansk oblast and, interestingly, the huge prevailing of the TB incidence in the general population over the incidence among the permanent residents in NAD, are both phenomena that need clarification.…”
Section: Discussionmentioning
confidence: 99%
“…По мере прогрессирования пандемии борьба приобрела статус более ответственной задачи и потребовала подхода, охватывающего все мировое сообщество. В целях координации всеобщего противодействия распространению новой коронавирусной инфекции, которая «убивает людей, распространяя человеческое страдание и разрушение», ООН приняла официальные рекомендации «Общая ответственность, глобальная солидарность: реагирование на социально-экономические последствия КОВИД-19» 1 .…”
unclassified